The comparison of the effect of garlic and lemon juice on blood pressure and comfort in hypertensive patients. - Bahrani, Seyed shahabeddin; Abdulkarimi, Rahim; sabziyani, Zahra; Zahrakord; Mohamadi, Maryam Agha; Gomar, Erfan; kord, Zohre; Afshari, Sahar; Bozorg, Mohadese Jame (Revista Latinoamericana de Hipertensión, 2020)
High blood pressure is one of the biggest causes of disease and mortality in the world and the prevalence of high blood pressure and people affected by it is increasing in the world. The use of non-pharmacological methods such as complementary medicine can play an important role in the process of controlling and modulating blood pressure in patients with high blood pressure. The aim of this study was to compare the effect of garlic and lemon juice on blood pressure levels and comfort of patients with hypertension. This study was performed as a three-group clinical trial by repeated measures in 101 patients with primary hypertension referred to Farshchian Heart Hospital in Hamadan in 1397 who met the inclusion criteria. Patients were selected by convenience sampling and randomly divided into one of three groups: lemon juice, garlic and control. First, patients' blood pressure and comfort level were measured in three groups: in the group of garlic, 10 grams of garlic daily after breakfast and 10 grams of garlic after dinner, and in the group of lemon juice, 10 cc of lemon juice daily after breakfast and 10 cc after After dinner, eat for 20 days and then rest for a week. During this week, the patient's blood pressure and comfort were measured, and this was repeated for another 20 days, and the patients' blood pressure and comfort were measured again after 20 days. In the control group, only the usual treatment was received and their blood pressure and comfort were measured simultaneously with the other groups. Data were analyzed using SPSS 22 software and statistical tests such as Chi-square, ANOVA, ANCOVA and repeated measures ANOVA. The results of Repeated measures ANOVA test showed that there was a statistically significant difference between the mean systolic and diastolic blood pressure and the comfort of patients in the three groups in the three stages of the study (before, during and after) (P <0.001). Significance of garlic and lemon juice consumption leads to lowering blood pressure levels and increasing patient comfort, but no difference was observed between garlic and lemon juice groups. According to the results of the study, patients with hypertension can increase their comfort level by using lemon juice or garlic and have better control over their blood pressure levels.